Characteristics of meltwater export from Jakobshavn Isbræ and Ilulissat Icefjord. Issue 74 (4th September 2017) - Beaird, Nicholas; Straneo, Fiammetta; Jenkins, William
ABSTRACT: Jakobshavn Isbræ, which terminates in Ilulissat Icefjord, has undergone rapid retreat and is currently the largest contributor to ice-sheet mass loss among Greenland's marine terminating glaciers. Accelerating mass loss is increasing fresh water discharge to the ocean, which can feed back on ice melt, impact marine ecosystems and potentially modify regional and larger scale ocean circulation. Here we present hydrographic observations, including inert geochemical tracers, that allow the first quantitative description of the glacially-modified waters exported from the Jakobshavn/Icefjord system. Observations within the fjord suggest a deep-reaching overturning cell driven by glacial buoyancy forcing. Modified waters containing submarine meltwater (up to 2.5 ± 0.12%), subglacial discharge (up to 6 ± 0.37%) and large portions of entrained ocean waters are seen to exit the fjord and flow north. The exported meltwaters form a buoyant coastal gravity current reaching to 100 m depth and extending 10 km offshore.